Production model under the integrated approach of lean manufacturing and SLP to increase efficiency in a company of the metal mechanic sector - Barreto Guillen, Marcelo Augusto (2024)
Metal mechanics plays a relevant role in the entire productive structure of the economy since it is an indispensable supplier of capital goods such as equipment, infrastructure, spare parts, and machines. However, the lack of efficient production processes, the high rate of defective products, and unnecessary routes in factories and production workshops are some of the frequent problems that companies in this area have that directly affect their productivity. Consequently, extreme routes and the profiling area have been identified as the main bottlenecks in the production process, impacting production efficiency. Therefore, the main objective of this case study is to demonstrate how the implementation of Lean tools has managed to increase the efficiency of the process for the production of thermoacoustic panels, reducing unnecessary routes and defective products. The proposed model comprises Lean tools such as the standardization of work and the 5S methodology, and the SLP was also applied to carry out the redistribution of activities. A simulation was carried out in the Arena software to validate the improvement proposal's results. The results obtained from the simulation were an increase of 19.24% in the overall efficiency of the process, a decrease of 42.4% in hours lost due to defective products, and a 26.7% reduction in downtime